An Analysis of Student’s English Proficiency through Problem Based Learning Model (A Study on Fifth Semester Students of Tadris Bahasa Inggris) - Pratiwi, Riris Septi (Lembaga Riset dan Inovasi Almatani, 2025)
This study aims to analyze English language skills through the Problem-Based Learning model. English language skills refer to a person's ability to communicate effectively in English. This ability includes various aspects such as reading, writing, speaking, and listening. This study uses a qualitative descriptive method. Respondents in this study were the fifth students of English Language Education UINFAS Bengkulu. Data were obtained from interviews and observations. The data that had been obtained were analyzed using three stages, namely data reduction, data display, conclusion, and verification. The results showed that the speaking ability of fifth-semester students in the English Language Education program was found to be that they can explain issues using their own words. Students are able to express ideas or opinions during the PBL (Problem-Based Learning) sessions. In listening skills, students showed a better understanding of oral materials because they were accustomed to listening and analyzing various discussions in problem-based learning sessions. Students are able to appreciate the ideas or opinions of their classmates and acquire new vocabulary. The problem-based learning model also made students are able to identify information or ideas in detail. They are capable of disregarding irrelevant information in the text. This indicates that one aspect of reading can be mastered by them. In writing skills, the results of the study showed that students who studied with PBL were able to write more structured and logically. Keywords : English Proficiency, Problem Based Learning Model